Analysis Of Occupational Safety And Health (Osh) Risk Management In The Advanced Phase Of A High-Rise Building Construction Project - Eko Budi Utomo; Budi Witjaksana; Jaka Purnama (Politeknik Negeri Batam, 2026)
This study aims to analyze the implementation of Occupational Safety and Health (OSH) risk management during the advanced stages of high-rise building construction projects. This stage is known for its high level of complexity, as it involves various concurrent work activities with overlapping risks. The research method employed is a descriptive qualitative approach through field observations and a literature review. Workplace accident analysis was conducted using the Injury Frequency Rate (IFR) and Injury Severity Rate (ISR) indicators, supported by a Poisson distribution approach to predict the likelihood of accidents. Additionally, risk identification and assessment were performed based on the AS/NZS 4360:2004 standard, considering both the likelihood and impact of risks. The research results indicate that during the observation period, no workplace accidents were recorded, with an IFR of 0, indicating an extremely low accident frequency rate. Meanwhile, the ISR value indicates a small number of lost workdays due to minor incidents. The implementation of the Occupational Safety and Health Management System on this project was assessed as having been carried out well and in accordance with applicable regulations, particularly regarding hazard identification, risk control, and preparedness for emergency conditions. These findings indicate that consistent and integrated risk management can create a safe work environment and support the smooth implementation of projects